Solving Nanofluid Flow Over a Permeable Stretching and Shrinking Surfaces using Shooting Technique - Ismail, Norhusnina Huda; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2023)
The analysis of nanofluid flow over permeable stretching and shrinking surfaces using the shooting technique with Runge-Kutta-Felhberg in Maple software. The governing equation of nanofluid on boundary layer flow was solved from the partial differential equation and transformed into a system of ordinary differential equations by using an appropriate similarity transformation. The nonlinear ordinary differential equations were considered for different types of nanoparticles, which are copper and silver. The problem was numerically handled to investigate the influence of the nanofluid’s solid volume fraction or nanoparticle volume fraction parameter. The results showed how the governing parameters affected the skin friction coefficient, local Nusselt number, temperatures, and velocity profiles. It was obtained that the nanoparticle volume fraction has a substantial impact on fluid flow and heat transfer characteristics.